Baharın Müjdecisi: Çiğdem (Crocus) ya da AN.TAH.ŠUMŠAR. Hititler Devri Anadolu Florasına Küçük Bir Katkı - Ertuğ, Füsun
Harbinger of Spring: Crocus, "Çi?dem" or AN.TAH.ŠUMŠAR. A Small Contribution to the Anatolian Flora of the Hittite Period